Socialization and Training for ISBN Book Creation for the Community in Collaboration with YPAD Publisher - Kurniawan, Angga; Tasrim; Tyagita Dianingtias Sudibyo; Epsilandri Septyarini; Ansri Jayanti (Yayasan Putra Adi Dharma, 2024)
The